PRAKTIK NOMINEE AGREEMENT OLEH WARGA NEGARA ASING SEBAGAI SARANA PENYELUNDUPAN HUKUM DI SEKTOR AGRARIA INDONESIA - Mutiara Rizkia; Zulfikar Jayakusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Many foreigners come to Indonesia to settle in the country, but are limited in their needfor housing and land. According to Indonesian law, foreigners cannot own property rights toland in Indonesia. Thus, foreigners choose a shortcut using a nominee agreement which isindicated as legal smuggling. Seeing the existence of foreign elements in the civil relations thatoccur, and the act of legal smuggling (wetsontduiking) which falls into the realm of PrivatInternational law (PIL). The purpose of this research is to find out the aspects of PIL in thepractice of nominee agreements on land by foreigners and to find out the legal consequencesof controlling land ownership rights carried out by foreigners through nominee agreements inIndonesia from an PIL perspective by first examining the legal force of nominee agreements.The results of this normative legal research are, nominee agreement is an agreementcontaining international aspects made between Indonesian citizens and someone whoaccording to the law cannot be the subject of property rights, namely in order to control landwith property rights. Nominee agreement is a form of legal smuggling to avoid the provisionsof Article 21 paragraph (1) in conjunction with Article 26 paragraph 2 of the UUPA. Based onArticle 1320 of the Civil Code, the nominee agreement does not fulfill the halal causa, so thatthe legal consequences are null and void. Legal smuggling results in fraus omnia corrumpit,namely that the legal act in its entirety is invalid.Keywords: Nominee- Legal Smuggling-Foreigners-Agrarian